Zum Problem der Hybridbildungen im Dänischen mit englischen Konstituenten - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2007)
The aim of the article is to describe loan blends (also called hybrids or nybrid creations) in the Danish language with English elements. Firstly, some definitions of the hybrids are presented and discussed and next new definitions are proposed. Finally, an approach to an analysis of examples existing in the Danish language is made.